COL5A3: A prognostic biomarker and potential therapeutic target in pancreatic cancer - Li, Yongjie; Zeng, Min; Wang, Ting; Jiang, Feng; Li, Chengjian (Molecular & Cellular Biomechanics, 2024)
Pancreatic cancer is a malignant tumor of the digestive system with a high mortality rate and a poor prognosis. While type V collagen 3 (COL5A3) is extensively expressed in many tumor tissues, its prognostic significance and immune infiltration in pancreatic cancer remain unknown. As a result, we investigated COL5A3’s predictive function in pancreatic cancer and its relationship to immune infiltration. COL5A3 is significantly expressed in pancreatic cancer tissues compared to normal tissues. High COL5A3 expression is associated with poor clinicopathological characteristics and a worse prognosis of pancreatic cancer. The Kaplan-Meier survival analysis revealed that pancreatic cancer patients with high COL5A3 expression had a poorer prognosis than those with low COL5A3 expression. According to the ROC curve, COL5A3 has high sensitivity and specificity in the detection of pancreatic cancer. Correlation studies revealed that COL5A3 mRNA expression is associated with immune cell infiltration. This work indicates for the first time that COL5A3 may be a novel predictive biomarker linked to immune infiltration, providing a new target for pancreatic cancer detection and therapy.